Características de gerenciamento da produtividade dos recursos de produção das empresas pertencentes ao APL calçadista da Paraíba - Souza, éverton Cristian Rodrigues de (2012)
The global situation compels the enterprises to the adoption of distinct posture from everything have been seen in the past, adopting advanced models of the manufacturing organization and seeking to establish strategic partnerships focused in the competitiveness. One of interorganizational partnership arrangements, based on the concept of coopetition, is the Local Productive Arrangement (APL). Among the typical characteristics of this type of business arrangement are the site location, with a focus on regional vocation exploration and intensive use of resources available at regional level. Thus, this dissertation presents the characteristics of management and productivity metrics productive resources of the component companies of the shoes maker APL in Paraíba, Brazil. In order to reach the proposed objectives were undertaken the following steps systematically: literature review, around themes related to APLs, management of productive resources and productivity, with a view to the composition of a framework that support theoretical research; site data collection, operationalized by a pre-structured questionnaire in order to obtain representative data of the object of study; and analysis of acquired data, under the lens of the themes around which orbits research . Among the results obtained in this study, it was found that the relationship is more pronounced between the enterprise and the institutional bodies that support the APL, and the relationship interenterprise is incipient. It was noted also that the cluster is composed mainly of micro and small businesses, being common, many of the manegement characteristics, identified by the literature as peculiar of that scope enterprises. It is an informal APL. The findings point also to the unsystematic management of enterprises, endowed with great content empiricism and neglect of modern management models. With regard to productivity management practices, it was found that only about a third of the companies surveyed do performance monitoring through productivity indicators, using partial indicators of character and punctual, not being representative of the company as a whole, which prevents monitoring evolving the company, mainly because there are no formal records of surveyed indicators, disabling monitoring or comparison with other companies. Thus we conclude that the arrangement object of study approaches a cluster of Micro and Smalls enterprises that act individualistically, failing in care of some essential factors to the development of an APL, listed in the literature. There is also the need for closer approaching between actors, including the common resource management by the firms, which will reduce the uncertainties of management and promote better flow of tacit knowledge of the cluster. We conclude, too, that while meeting the goals of its utilization, productivity rates adopted by companies studied only partially meet the criteria of selectivity proposed in the literature, particularly with regard to the contemplation of the strategic nature of productivity management.